2011
DOI: 10.1055/s-0030-1256166
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic closure of a rectovaginal fistula combiningN-2-butyl-cyanoacrylate (Histoacryl) and Resolution clips

Abstract: Rectovaginal fistulas (RVFs) are abnormal communications between the anterior wall of the rectum and the posterior vaginal wall. The incidence of RVFs is relatively low; most of them are related to obstetric injury [1]. Patients complain of uncontrollable passage of gas or feces from the vagina. RVFs may be managed both medically and surgically. Endoscopic approaches with endoclip closure of gastrointestinal fistula and injection of tissue adhesive have been proposed [2], but a combined approach using both met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Endoscopic clipping: Endoscopic clipping is another technology using endoclips to completely close gastrointestinal leaks and fistulas, initially applied for iatrogenic gastric perforation in 1993[ 44 ]. John et al [ 45 ] reported the first successful closure of an RVF with TTSCs, which was also applied for repair of refractory RVF[ 33 ]; Ortiz-Moyano et al [ 46 ] described a combined approach using TTSCs and tissue adhesive that improved the rate of technical success in the endoscopic clips treatment of RVFs, since clips not only worked in opposing the margins, but acted as a scaffold for the glue. OTSCs for the gastrointestinal tract had greater force and a consistently high mean rate of procedural success of 80%-100%, and a durable clinical success rate of 57%-100%, and was preferred over TTSCs for closure of gastrointestinal fistulas[ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Endoscopic clipping: Endoscopic clipping is another technology using endoclips to completely close gastrointestinal leaks and fistulas, initially applied for iatrogenic gastric perforation in 1993[ 44 ]. John et al [ 45 ] reported the first successful closure of an RVF with TTSCs, which was also applied for repair of refractory RVF[ 33 ]; Ortiz-Moyano et al [ 46 ] described a combined approach using TTSCs and tissue adhesive that improved the rate of technical success in the endoscopic clips treatment of RVFs, since clips not only worked in opposing the margins, but acted as a scaffold for the glue. OTSCs for the gastrointestinal tract had greater force and a consistently high mean rate of procedural success of 80%-100%, and a durable clinical success rate of 57%-100%, and was preferred over TTSCs for closure of gastrointestinal fistulas[ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…3,4 There have also been a few case reports of the use of fibrin or bioglue for the repair of RVFs, but only in a few select patients has it been successful. 5,6 One case reported the use of histoacryl as a sealant placed between endoclips after a 78-year-old female refused surgery and at follow-up was asymptomatic at 2 months. 5 Abel et al had the largest case report series with ten patients treated with a fibrin glue for a mixture of complex RVFs with 60% of patients having complete healing of the fistula.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 One case reported the use of histoacryl as a sealant placed between endoclips after a 78-year-old female refused surgery and at follow-up was asymptomatic at 2 months. 5 Abel et al had the largest case report series with ten patients treated with a fibrin glue for a mixture of complex RVFs with 60% of patients having complete healing of the fistula. 6 The reported failures were due to immuno-compromised states due to Crohn's disease and HIV, but the patients still reported decreased drainage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall experience with clips is limited to case reports alone that have shown success. 15,16 Endorectal and transvaginal advancement flaps are among the more popular techniques for RVF repair because of their familiarity by the surgical team and high procedure acceptance by patients. The average closure rates with these repairs are 60%.…”
Section: Treatmentmentioning
confidence: 99%